Building an Academic Transgender Medicine Center of Excellence: The 5-Year Johns Hopkins Experience. (3rd January 2023) - Marano, Andrew A.; Noyes, Melissa; Eisenbeis, Lauren; Hedian, Helene F.; Segna, Kara; Neira, Paula M.; Thomas, Kate; Lee, W.P. Andrew; Redett, Richard J.; Coon, Devin
Abstract : Gender-affirming care for transgender and gender diverse (TGD) individuals is a multidisciplinary endeavor that requires organized efforts of many specialized practitioners. TGD individuals experience many health care barriers, including the scarcity of multidisciplinary teams formed to coordinate and deliver complex care in an efficient and affirming way. The Johns Hopkins Center for Transgender Health was founded in 2017 with the mission of decreasing health disparities and improving the health of the TGD community. The authors present their experience building the center around a service line model in which patients have 1 point of contact, they are tracked throughout the care process, and the multidepartmental practitioners involved in their care are aligned. This model allowed for a patient-centered experience in which all involved disciplines were seamlessly integrated and the patient could navigate easily among them. With the structure and mission in place, the next challenge was to develop an infrastructure for culturally competent care. Through competency training and adjustment of systems-based logistics, measures were put in place to prevent traumatic experiences, such as misgendering, use of culturally inappropriate vocabulary, and use of incorrect names. Partnerships among colleagues in the fields of plastic surgery, urology, gynecology, otolaryngology, anesthesia, psychiatry/mental health, internal medicine, endocrinology, fertility, nursing, social work, speech therapy, and pediatrics/adolescent care were necessary to provide the appropriate breadth of services to care for TGD patients. Since its inception, the center has seen steady and continual growth, with more than 2, 800 patients in its first 5 years. By sharing their experience in creating and developing a center of excellence, the authors hope to provide a blueprint for others to expand health care quality and access for TGD individuals.